Aproveitamento do lodo gerado no tratamento de efluente da indústria de lavanderia têxtil na produção de bloco de cerâmica vermelha - Kaminata, Oswaldo Teruo (2008)
The textile laundry industries generate wastes of difficult treatment and final destination known as textile sludge, consisting of organic matter and other chemical elements called heavy metals. The disposition, treatment and recycling of such waste is of great interest to the companies that produce them. Aiming to contribute for the reduction of the environmental impact caused by the disposal of this waste to the environment, this study evaluated an alternative for waste recycling of textile industrial laundries by means of incorporating it in the mass of clay blocks for the manufacture of ceramic seals, used in construction. In order to determine the best treatment, the mixed textile residue was characterized, and later on incorporated into the mass of clay for the manufacture of ceramic blocks sealing in small scale (63 mm x 30 mm x 47 mm) in percentages of 5%, 10% , 15%, 20% and 25% by weight, including blocks of control made only with clay. The quality of blocks produced in small scale was measured by tests of resistance to compression, water absorption, retention capacity of heavy metals, as measured by tests of leaching and solubilization. The results showed that it is possible to incorporate up to 15% of textile waste in the manufacture of ceramic blocks, without losing their essential qualities. Aiming the possibility of production on an industrial scale, samples of ceramic blocks in real scale with the formulation of 15% of textile waste were produced and characterized. For blocks in real scale, the strength of adhesion to the mortar, chemical speciation and statistical treatment in the mass balance were also determined. The results of the performed tests are within the limits set in standards of the Associação Brasileira de Normas Técnicas. The use of textiles waste can increase the efficiency of the industries involved in the manufacture of ceramic blocks, promoting a reduction in extraction of the natural resource used, as well as provide a sustainable destination of the pollutant waste to the laundry textile industry.